Wolskie memuary. Wola Krzysztoporska we wspomnieniach Heleny Szereszewskiej, Włodzimierza Dajcza i Jana Kodrębskiego. Egzemplifikacje na marginesie historii antropologicznej i historii regionalnej - Latocha, Sebastian (Zeszyty Wiejskie, 2016)
There are three published personal diaries related to Wola Krzysztoporska: Józef i Hana. Kronika rodziny Szpilfoglów z Krysztoporskiej Woli (by Helena Szereszewska), Odłamki czasu (by Włodziemierz Dajcz) and Ze świadectwa profesora Jana Kodrębskiego (by Jan Kodrębski). The diaries are unacknowledged but magnificent and invaluable sources to ethno- history and local history of Wola Krzysztoporska. The nature of the diaries depicts the history that is remembered and mythologized. They duck out of the categories: truth and untruth. It makes them inexact, but beautiful. They do not present the objective history of Wola Krzysztoporska but subjective memories full of myths and nostalgia.